The Economic Aspects of Sovereignty and Self-Determination in Contemporary International Law. Basic Issues - Tyranowski, Jerzy (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2021)
The paper is an English translation of Ekonomiczne aspekty suwerenności i samostanowienia we współczesnym prawie międzynarodowym (zagadnienia podstawowe) by Jerzy Tyranowski, published originally in Polish in “Ruch Prawniczy, Ekonomiczny i Socjologiczny” in 1992. The text is published as a part of a jubilee edition of the “Adam Mickiewicz University Law Review. 100th Anniversary of the Department of Public International Law” devoted to the achievements of the representatives of the Poznań studies on international law.